In silico analysis of Hepatitis C virus (HCV) polyprotein domains and their comparison with other pathogens and allergens to gain insight on pathogenicity mechanisms. (December 2016) - Patel, Seema
Graphical abstract: Highlights: Hepatitis C (HCV) is a Flaviviridae family virus causing acute or chronic liver inflammation. This in silico study analyses UniProt-retrieved HCV protein domains, using SMART tool and tailor-made scripts. Based on the results, insights on pathogenesis were garnered and hypotheses were formulated, worthy of empirical studies. Abstract: Hepatitis C (HCV) is a deadly virus from family Flaviviridae, causing acute or chronic liver inflammation. Given its lethality and no known vaccine to curb it, understanding its pathogenic mechanism is critical. By analyzing the domains in its protein sequence, a plethora can be learnt about its immune manipulation strategies. In this regard, current in silico study compares publicly-available HCV polyprotein sequences and their domain profiles. Apart from using UniProt sequences and SMART (Simple modular architecture research tool) platform for domain profiling, a set of customized scripts were developed to extract the patterns of protein domain distribution. Also, the total domain set in representative HCV polyprotein sequences were compared with that of other viral pathogens (Ebola, HIV, Dengue, Zika) and allergens (plant pollen, cockroach allergens) to find the conserved domains of key role in pathogenesis.